Rational Design, Synthesis and Biological Evaluation of Novel Pyrazoline-Based Antiproliferative Agents in MCF-7 Cancer Cells - Mariam M. Fakhry; Kazem Mahmoud; Mohamed S. Nafie; Ahmad O. Noor; Rawan H. Hareeri; Ismail Salama; Safaa M. Kishk (MDPI AG, 2022)
Breast cancer is a disease in which cells in the breast divide continuously without control. There are great limitations in cancer chemotherapy. Hence, it is essential to search for new cancer therapeutics. Herein, a novel series of EGFR/HER2 dual inhibitors has been designed based on the hybridization of thiazole and pyrazoline fragments. The synthesized compounds were screened for their anti-proliferative activity against MCF-7 breast cancer cell line and MCF-10 normal breast cell line. Interestingly, synthesized compounds 6e and 6k showed very potent antiproliferative activity towards MCF-7 with IC50 values of 7.21 and 8.02 µM, respectively. Furthermore, enzymatic assay was performed against EGFR and HER2 to prove the dual inhibitory action. Compounds 6e and 6k showed potent inhibitory activity for EGFR with IC50 of 0.009 and 0.051 µM, respectively, and for HER2 with IC50 of 0.013 and 0.027 µM, respectively. Additionally, compounds 6e and 6k significantly stimulated apoptotic breast cancer cell death. Compound 6e was further explored for its anticancer activity in vivo using a Xenograft model. Moreover, computational modeling studies, ADMET studies and toxicity prediction were performed to investigate their potential drug candidates.